1997
DOI: 10.1021/np970054v
|View full text |Cite
|
Sign up to set email alerts
|

Bripiodionen, a New Inhibitor of Human Cytomegalovirus Protease from Streptomyces sp. WC76599

Abstract: Bripiodionen (1), a new natural product, was isolated from Streptomyces sp. WC76599 during the screening of microbial fermentation extracts for their ability to inhibit human cytomegalovirus protease. The structure of 1 was elucidated by spectroscopic methods. Compound 1 displayed inhibitory activity against human cytomegalovirus protease with an IC50 value of 30 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…The relative positions of C-13 and C-14 was assigned from the lower filed proton signal of H 3 -14 ( δ H 2.10) than H 3 -13 ( δ H 1.74) due to the deshielding effect of 4-carbonyl group. The remaining 1 H and 13 C NMR signals and the HMBC correlations of HN-1 ( δ H 9.79) to C-3 ( δ C 103.2), C-4 ( δ C 183.3) and C-5 ( δ C 129.3) ( Figure 2 and Figure S7 ), along with the careful comparison with known bripiodionen [ 14 ], suggested a 2,4-pyrrolidinedione moiety. Thus, compound 1 had the same core as bripiodionen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative positions of C-13 and C-14 was assigned from the lower filed proton signal of H 3 -14 ( δ H 2.10) than H 3 -13 ( δ H 1.74) due to the deshielding effect of 4-carbonyl group. The remaining 1 H and 13 C NMR signals and the HMBC correlations of HN-1 ( δ H 9.79) to C-3 ( δ C 103.2), C-4 ( δ C 183.3) and C-5 ( δ C 129.3) ( Figure 2 and Figure S7 ), along with the careful comparison with known bripiodionen [ 14 ], suggested a 2,4-pyrrolidinedione moiety. Thus, compound 1 had the same core as bripiodionen.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated that 1a and 1b were a pair of rapidly interconverting E / Z geometric isomers in solution. Bripiodionen and apiodionen also displayed a similar equilibrium [ 14 , 15 ]. We carried out theoretical calculations of energy for stable conformers of 1a and 1b .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…225b (SS 225b). The replication of human immunodeficiency virus type 1 (7) and cytomegalovirus (26) were also efficiently inhibited by proteinase inhibitors, produced by Streptomyces species.…”
Section: The Application Of Ss 34-1 Induced a Continuous Rise Of Thmentioning
confidence: 99%
“…And, screening of natural products has also yielded several compounds that have IC 50 values in low µM range. They include bripiodionen from Streptomyces [118] for CMV protease, a cycloartanol sulfate from the green alga Tuemoya sp. for both VZV and CMV proteases [119].…”
Section: A Structure Genomics and Drug Discoverymentioning
confidence: 99%